Two outbreaks of Salmonella enteritidis phage type 4 infection associated with the consumption of fresh shell-egg products. - Cowden, J. M. (Cambridge University Press, 1989)
In 1988 there were two outbreaks of infection with Salmonella enteritidis phage type 4 in adjacent local authorities. The first affected 18 of 75 helpers and guests who attended a private function. Investigations revealed that home-made vanilla ice-cream containing uncooked eggs was the vehicle of infection and the causative organism was identified at the premises of the egg producer. The second affected 84 of 422 delegates attending a conference dinner, and 12 of 50 hotel staff at risk. A dessert made with lightly-cooked egg yolk and raw egg white was associated with infection, and the epidemic strain was cultured from the shell of an egg and an environmental sample from the producer's farm. It is of interest that one outbreak involved free-range and one battery-produced eggs, and that in one the vehicle was prepared at home and in the other in commercial premises. In neither incident was any deficiency in standards of egg production or catering practice discovered.